How does a woman with Alzheimer's disease make sense of becoming cared for?. (November 2016) - Borley, Gayle; Sixsmith, Judith; Church, Sarah
This case study explores the meaning one woman with Alzheimer's disease (AD) gives to receiving assistance with instrumental activities of daily living (IADLs) from her spouse. Improving the care of people living with AD is widely accepted as an important outcome in dementia services. Understanding how it feels for the person with AD to receive that care is essential to enhance their quality of life. Experiences identified using interpretative phenomenological analysis focus on a connection to past self and maintaining identity whilst also accepting change. The experience of 'Sameness and Change' identifies her feelings of discontinuity whilst 'Goodness' depicts her continued emotional expression of care presented in an attempt to remain someone of value within her family. These findings offer new insight and understanding to assist a woman's transition from carer to becoming cared for.